Impact of Exclusive Breastfeeding on Anthropometry, Morbidity and Duration of Hospitalization of Infants Under Six Months of Age - Km., Roma; Bist, Aayush; Khetan, Shivam; Pokhrel, Amrit; Oli, Eliza; Acharya, Niraj (Journal of Nepalgunj Medical College, 2023)
Introduction: Breast milk is the best feed for the infants. Breast milk has got several immunological benefits protecting the infants from various infectious diseases and some chronic diseases of adulthood. Exclusively breastfed babies get less infected and have proper growth and development. Aims: To study the impact of exclusive breastfeeding on morbidity and hospital stay of infants of four weeks to six months of age. Methods: This was a hospital based cross sectional study done at Pediatric department of Nepalgunj Medical College, Nepalgunj, a tertiary care referral hospital in Nepal, conducted over a period of one year from January 2022 - December 2022. All the infants meeting the inclusion criteria were included for the study. Results: A total of 278 infants of 4 weeks to 6 months of age meeting inclusion criteria were included. More than sixty four percent infants were exclusively breastfed. The majority of patients belonged to modified kuppuswamy class 3. Significant impact on nutritional outcome was seen with feeding pattern as 1.7 higher times chance of being underweight in breastfeeding along with supplementary feeding with a highly significant p value of 0.002. Exclusively breastfed infants suffering from respiratory diseases, gastroenteritis, fever and due to other various morbidities were hospitalized for less than one week. Morbidity and hospital stay had a statistically significant relationship with feeding pattern. Higher morbidity was observed due to various diseases of infancy like respiratory diseases, gastroenteritis, sepsis, etc. in breastfeeding along with supplementary feeding group as compared to exclusively breastfeeding group. Conclusion: Statistically significant association was found in terms of morbidity, hospital stay and feeding pattern amongst exclusively breastfed infants and breastfeeding along with supplementary fed infants. Less morbidity and shorter hospital stay was observed in exclusively breastfed infants as compared to breastfeeding along with supplementary feeding infants.